Respuesta :

Answer:

x=3, y=3

Step-by-step explanation:

If we plug in 3 for each variable, their sum is 6, and the first equation will be true.

Answer:

[tex]x=y=3[/tex]

Step-by-step explanation:

Given Equation:

[tex]2x+3y=15[/tex]   Equation:1

[tex]x+y=6[/tex]        

or [tex]x=6-y[/tex]      Equation:2

Using Substitution method, put the value of 'x' in equation:1

[tex]2x+3y=15[/tex]

[tex]2(6-y)+3y=15\\\\2(6)-2(y)+3y=15\\\\12-2y+3y=15\\\\12+y=15\\\\[/tex]

Subtracting '12' both sides:

[tex]12+y-12=15-12\\\\y=15-12\\\\y=3\\\\[/tex]

Putting value of 'y' in equation:2

[tex]x=6-y[/tex]

[tex]x=6-3\\\\x=3[/tex]

So, the values are:   [tex]x=y=3[/tex]

ACCESS MORE